Whole transcriptome analysis and construction of gene regulatory networks of granulosa cells from patients with polycystic ovary syndrome (PCOS) - Yuan Yuan; Daiterigele; Qian Zhang; Chen Du (European Journal of Medical Research)
Abstract Objective Polycystic ovary syndrome (PCOS) is a reproductive endocrine disease characterized by reproductive dysfunction and metabolic abnormalities. The purpose of this study was to explore the expression characteristics of coding and non-coding RNAs in granulosa cells of PCOS, and to provide data support for understanding the pathogenesis of PCOS. Methods Three patients with PCOS (according to the 2003 Rotterdam diagnostic criteria) and three normal controls were selected. We used the standard long protocol to collect granulosa cells from two groups, who underwent assisted reproduction at the Reproductive Medicine Center of the Affiliated Hospital of Inner Mongolia Medical University, China. We performed whole-transcriptome sequencing using RNA-Seq technology to construct transcriptome patterns of messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs). These patterns were then subjected to in-depth analysis using bioinformatics tools. Results We identified a total of 2111 mRNAs and 4328 non-coding RNAs (ncRNAs) in the PCOS group as compared with the control group. Among the ncRNAs, there were 2047 lncRNAs, 892 circRNAs, and 1389 miRNAs. Based on the condition |log2(fold_change) |≥ 1 and a P-value of ≤ 0.05, we obtained 705 differentially expressed genes (DEGs), 204 differentially expressed lncRNAs, 111 differentially expressed circRNAs, and 88 differentially expressed miRNAs. The target genes were mainly enriched in metabolic pathways such as mitogen-activated protein kinase (MAPK), Wnt, transforming growth factor-beta (TGF-β), and the cell cycle. There were three types of circRNAs, among which the number of exon-type circRNAs accounted for more than 90%. Using co-expression network analysis, we identified several important candidate gene mRNAs (VLDLR, PPP2R2B, and MYOCD), lncRNAs (FBXO30, SNHG14, and PVT1), and miRNAs (miRNA-150); these mRNAs and ncRNAs could play a regulatory role in PCOS granulosa cells. Conclusion In this study, we discovered significant alterations in mRNAs, lncRNAs, circRNAs, and miRNAs in PCOS granulosa cells, indicating dysregulation in vital pathways. Notably, genes like VLDLR, PPP2R2B, and MYOCD, along with lncRNAs FBXO30, SNHG14, and PVT1, may contribute to PCOS pathology, shedding light on potential therapeutic targets.